Behçet's Syndrome as a Model of Thrombo-Inflammation: The Role of Neutrophils - Emmi, Giacomo; Becatti, Matteo; Bettiol, Alessandra; Hatemi, Gülen; Prisco, Domenico; Fiorillo, Claudia (Frontiers in Immunology, 2019)
Behçet's syndrome (BS) is a systemic vasculitis, clinically characterized by different organ involvement and often complicated by thrombosis which occurs in vessels of all sizes. Thrombosis is more frequent in male patients with active disease and represents an important cause of morbidity and mortality. Neutrophil involvement in BS has been repeatedly suggested in the last few years. Indeed, neutrophils have been shown to be hyperactivated in BS patients, probably with a HLAB51 related contribution, and represent the main cells infiltrating not only oral and genital ulcers or erythema nodosum, but also other sites. Besides being deputed to host defense against micro-organisms, neutrophils display fundamental roles both in inflammation and tissue damage becoming inappropriately activated by cytokines, chemokines and autoantibodies and subsequently producing large amounts of superoxide anion (O2.) via NADPH oxidase (NOX2). The strict relationship between inflammation and hemostasis has been already demonstrated. Indeed, inflammation and immune-mediated disorders increase the risk of thrombosis, but the pathways that link these processes have not been completely elucidated. In this regard, we recently demonstrated, in a large population of BS patients, a new neutrophil-dependent pathogenetic mechanism of thrombosis. In particular, it was shown that neutrophils, mainly through NADPH oxidase, produce excessive amounts of reactive oxygen species (ROS), which are able to markedly modify the secondary structure of fibrinogen and hence the overall architecture of the fibrin clot that becomes less susceptible to plasmin-induced lysis. These data point out that BS represents “per se” a model of inflammation-induced thrombosis and suggest that neutrophils specifically contribute to thrombo-inflammation in this rare disease. In particular, it is suggested that an alteration in fibrinogen structure and function are associated with enhanced ROS production via neutrophil NADPH oxidase. Altogether, these findings improve our understanding of the intricate pathogenetic mechanisms of thrombo-inflammation and may indicate potential new therapeutic targets.